A bead based multiplex immunoassay detects Piscine orthoreovirus specific antibodies in Atlantic salmon (Salmo salar). Issue 63 (April 2017) - Teige, Lena Hammerlund; Lund, Morten; Haatveit, Hanne M.; Røsæg, Magnus Vikan; Wessel, Øystein; Dahle, Maria K.; Storset, Anne K.
Abstract: Future growth in aquaculture relies strongly on the control of diseases and pathogens. Vaccination has been a successful strategy for obtaining control of bacterial diseases in fish, but for viral diseases, vaccine development has been more challenging. Effective long-term protection against viral infections is not yet fully understood for fish, and in addition, optimal tools to monitor adaptive immunity are limited. Assays that can detect specific antibodies produced in response to viral infection in fish are still in their early development. Multiplex bead based assays have many advantages over traditional assays, since they are more sensitive and allow detection of multiple antigen-specific antibodies simultaneously in very small amounts of plasma or serum. In the present study, a bead based assay have been developed for detection of plasma IgM directed against Piscine orthoreovirus (PRV), the virus associated with the disease Heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon. Using recombinant PRV proteins coated on beads, antibodies targeting the structural outer capsid protein μ1 and the non-structural protein μNS were detected. Results from a PRV cohabitation challenge trial indicated that the antibody production was initiated approximately two weeks after the peak phase of PRV infection, coinciding with typical HSMI pathology. Thereafter, the antibody production increased while the epicardial inflammation became less prominent. In conclusion, the novel assay can detect PRV-specific antibodies that may play a role in viral defence. The bead-based immunoassay represents a valuable tool for studies on HSMI and possibly other diseases in aquaculture. Graphical abstract: Highlights: Bead based assay detects IgM specific for Piscine orthoreovirus proteins μ1 and μNS. PRV- specific IgM is produced two weeks after infection of Atlantic salmon. Increasing PRV- specific IgM coincides with decreased PRV-associated epicarditis.